2013
DOI: 10.1080/09639284.2013.847322
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Students' Reflections on a Course to Enhance their Interpersonal Skills

Abstract: Communication skills are critical for an accountant's workplace success; however accounting education research to date has mainly focused on the writing and presentation skills aspects of communication skills. Research on developing accounting students' interpersonal skills has received scant attention. This paper provides an example of how to incorporate interpersonal skills into the accounting curriculum. Details are given on how to execute the course to promote effective, positive student outcomes. Examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
(58 reference statements)
0
10
0
2
Order By: Relevance
“…Students, practising accountants and, especially, the clients they serve would benefit. Furthermore, following Daff (2013) and Butler (2016) it recommends academic accountants to engage in and report on experiments to foster the inculcation of listening skills within accountancy courses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Students, practising accountants and, especially, the clients they serve would benefit. Furthermore, following Daff (2013) and Butler (2016) it recommends academic accountants to engage in and report on experiments to foster the inculcation of listening skills within accountancy courses.…”
Section: Resultsmentioning
confidence: 99%
“…The need is the more necessary in that accountancy students are shown to have lower emotional intelligence skills than students in, say, liberal arts programs, see Jones & Abraham (2009) and Cook et al (2011). Furthermore, accountancy students are more 'apprehensive' than others in engaging in oral communication (Daff 2013). Interestingly, a recent study found that graduating accountancy students regarded listening [and reading] skills the least important communication skills related to employability ('negating the views of employers who perceive them to be highly essential for new accountants' (Pia Patricia 2017)).…”
Section: Previous Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the optimal choice of the learning place represents the most important decision while the optimal choice of the pedagogic instruments is secondary. Thereby, the paper further adds to the literature analyzing how soft skills can be enhanced in the classroom (see, e.g., Nealy, 2005, John, 2009, De Villiers, 2010, Shah, 2013, Daff, 2013, Gil, 2013, Thomas et al, 2014.…”
Section: In Order To Strengthen the Dual Training System Continuing mentioning
confidence: 99%